Response of Central Nervous System Biomolecules and Systemic Biomarkers to Aerobic Exercise Following Concussion: A Scoping Review of Human and Animal Research - Dean M. Cordingley; Izabella Marquez; Serena C. L. Buchwald; Frederick A. Zeiler (Neurotrauma Reports)
The purpose of this study was to identify the response of biomolecules and biomarkers that are associated with the central nervous system to aerobic exercise in human and pre-clinical models of concussion or mild traumatic brain injury (TBI), and to highlight the knowledge gaps in the literature. A systematic scoping review was conducted following a search of EMBASE, MEDLINE, SCOPUS, BIOSIS, and Cochrane Libraries performed on September 8, 2023 (from data base inception). The scoping review was reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews. Duplicates were removed and article screening was performed using an online systematic review management system. The search resulted in a total of 2,449 articles being identified, with 14 articles meeting the inclusion/exclusion criteria and having their data extracted. One study was conducted in humans, while the remainder of identified studies utilized murine models. The current literature is limited and evaluated many different biomolecules and biomarkers with brain-derived neurotrophic factor being the most researched. Further studies on this topic are needed to better understand the biomarker response to exercise after concussion and mild TBI, especially in the human population.